Analysis of the Effectiveness of Rural and Urban Land and Building Tax (PBB-P2) Revenue on Local Original Revenue (PAD) in Mamuju Regency - Ikbal Ikbal; Haslindah Haslindah (Universitas Muhammadiyah Makassar, 2023)
This research was conducted at the Mamuju Regency Government with the main aim of evaluating the level of effectiveness and contribution of Rural and Urban Land and Building Tax (PBB-P2) in the region. The research methods used include analytical descriptive research and explanatory research. This research aims to describe the reality or condition of the research object, namely PBB-P2 in Mamuju Regency, by collecting data from related parties in the form of sentence descriptions. The research results reveal that the Rural and Urban Land and Building Tax in Mamuju Regency is classified as ineffective. This can be seen from the level of PBB-P2 revenue during the 2016-2018 period, which has consistently been below 60%, 39.55% to be precise. This low level of revenue indicates that the potential revenue from PBB-P2 has not been utilized optimally by local governments, so there is a need to identify and overcome obstacles that hinder the effectiveness of this tax. Nevertheless, this research also provides a basis for the Mamuju Regency Government to make improvements in the management of PBB-P2, such as increasing public awareness about tax obligations, improving the tax collection system, and increasing transparency in the use of tax revenues to advance development in the area. With these corrective steps, it is hoped that PBB-P2's contribution can increase, support local development, and provide greater benefits for the people of Mamuju Regency.